The new Oxford handbook of economic geography - Clark, Gordon L.,; Gertler, Meric S.,; Feldman, Maryann P.,; Wójcik, Dariusz, 1972- (Oxford handbooks online., 2018)
Sixty-six leading economists and geographers from around the world investigate the rival theories and perspectives that have sustained the development of economic geography. Building on the success of the hugely influential first edition, this volume offers a radically revised, updated, and broader approach to economic geography.